2012
DOI: 10.1111/j.1574-6968.2012.02540.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome shotgun sequencing of one Colombian clinical isolate of Mycobacterium tuberculosis reveals DosR regulon gene deletions

Abstract: Several genomes of different Mycobacterium tuberculosis isolates have been completely sequenced around the world. The genomic information obtained have shown higher diversity than originally thought and specific adaptations to different human populations. Within this work, we sequenced the genome of one Colombian M. tuberculosis virulent isolate. Genomic comparison against the reference genome of H37Rv and other strains showed multiple deletion and insertions that ranged between a few bases to thousands. Exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…To investigate the biological pathways and critical processes in the pathogenesis of TB potentially mediated by circulating monocytes, we first analyzed the systemic effect of TB on the baseline genome-wide gene expression profiles of MoTB compared to MoCT. Second, MoCT and MoTB were infected for 6 h at a multiplicity of infection of 10:1 with two Colombian clinical isolates of Mtb, UT127 and UT205, that may differ in virulence (Isaza et al, 2012;Duque et al, 2014;Baena et al, 2019), and then their transcriptional profiles were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the biological pathways and critical processes in the pathogenesis of TB potentially mediated by circulating monocytes, we first analyzed the systemic effect of TB on the baseline genome-wide gene expression profiles of MoTB compared to MoCT. Second, MoCT and MoTB were infected for 6 h at a multiplicity of infection of 10:1 with two Colombian clinical isolates of Mtb, UT127 and UT205, that may differ in virulence (Isaza et al, 2012;Duque et al, 2014;Baena et al, 2019), and then their transcriptional profiles were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…A posterior study (Duque et al, 2014) indicated that infection of human monocytes (MOI 10:1) with UT205 for 24 h induced a higher proportion of cells with membrane damage compared to UT127, suggesting differences in virulence between these two isolates. We also sequenced the genomes of both isolates (Isaza et al, 2012;Baena et al, 2019), which are 99.6% identical. Interestingly, they display significant transcriptomic differences when growth in axenic media (Baena et al, 2019) besides their extensive genomic similarity.…”
Section: Mycobacterium Tuberculosis Clinical Isolatesmentioning
confidence: 99%
“…Although this system has been extensively characterized at the molecular level, there are some observations, including one mentioned above, which are yet to be explained. For example, clinical isolates of M. tuberculosis from Colombia have recently shown to harbour a 3.6 kb deletion resulting in a loss of the DevR regulon genes [106]. The strain appears to have retained its virulence despite the lack of this apparently virulence determining gene segment.…”
Section: Mathematical Modelling Of Two-component Signallingmentioning
confidence: 98%
“…It is important to note that recently, Isaza et al [100] identify a haloalkane dehalogenasa (LinB) belonging to Mycobacterium tuberculosis CDC1551. This protein of 300 aminoacids, showed 100% homology to Mycobacterium tuberculosis KZN 605, Mycobacterium bobis BCG STR Pasteur 117 and 98% homology to Sphingobiun francensis and Sphingobiun sp.…”
Section: Biodegradation Pathways Of Hexachlorocyclohexanementioning
confidence: 99%